Residing in urban areas with higher green space is associated with lower mortality risk: A census-based cohort study with ten years of follow-up - Bauwelinck, Mariska; Casas, Lidia; Nawrot, Tim S.; Nemery, Benoit; Trabelsi, Sonia; Thomas, Isabelle; Aerts, Raf; Lefebvre, Wouter; Vanpoucke, Charlotte; Van Nieuwenhuyse, An; Deboosere, Patrick; Vandenheede, Hadewijch (Environment international, 2021)
•Large prospective cohort study in more than 2 million adult urban residents.•Non-accidental and cardio-respiratory mortality over long-term ten years follow-up.•Various objective and subjective green space indicators evaluated.•Inverse relations observed for non-accidental and respiratory mortality. Epidemiological studies suggest that residing close to green space reduce mortality rates. We investigated the relationship between long-term exposure to residential green space and non-accidental and cardio-respiratory mortality. We linked the Belgian 2001 census to population and mortality register follow-up data (2001–2011) among adults aged 30 years and older residing in the five largest urban areas in Belgium (n = 2,185,170 and mean follow-up time 9.4 years). Residential addresses were available at baseline. Exposure to green space was defined as 1) surrounding greenness (2006) [normalized difference vegetation index (NDVI) and modified soil-adjusted vegetation index (MSAVI2)] within buffers of 300 m, 500 m, and 1000 m; 2) surrounding green space (2006) [Urban Atlas (UA) and CORINE Land Cover (CLC)] within buffers of 300 m, 500 m, and 1000 m; and 3) perceived neighborhood green space (2001). Cox proportional hazards models with age as the underlying time scale were used to probe into cause-specific mortality (non-accidental, respiratory, COPD, cardiovascular, ischemic heart disease (IHD), and cerebrovascular). Models were adjusted for several sociodemographic variables (age, sex, marital status, country of birth, education level, employment status, and area mean income). We further adjusted our main models for annual mean (2010) values of ambient air pollution (PM2.5, PM10, NO2 and BC, one at a time), and we additionally explored potential mediation with the aforementioned pollutants. Higher degrees of residential green space were associated with lower rates of non-accidental and respiratory mortality. In fully adjusted models, hazard ratios (HR) per interquartile range (IQR) increase in NDVI 500 m buffer (IQR: 0.24) and UA 500 m buffer (IQR: 0.31) were 0.97 (95%CI 0.96–0.98) and 0.99 (95%CI 0.98–0.99) for non-accidental mortality, and 0.95 (95%CI 0.93–0.98) and 0.97 (95%CI 0.96–0.99) for respiratory mortality. For perceived neighborhood green space, HRs were 0.93 (95%CI 0.92–0.94) and 0.94 (95%CI 0.91–0.98) for non-accidental and respiratory mortality, respectively. The observed lower mortality risks associated with residential exposure to green space were largely independent from exposure to ambient air pollutants. We observed evidence for lower mortality risk in associations with long-term residential exposure to green space in most but not all studied causes of death in a large representative cohort for the five largest urban areas in Belgium. These findings support the importance of the availability of residential green space in urban areas.